Integrated process approach for degradation of p-cresol pollutant under photocatalytic reactor using activated carbon/TiO2 nanocomposite: application in wastewater treatment - Singh T.; Pal D.B.; Bhatiya A.K.; Mishra P.K.; Hashem A.; Alqarawi A.A.; AbdAllah E.F.; Gupta V.K.; Srivastava N. (My University, 2025)
Over the years, biodegradation has been an effective technique for waste water treatment; however, it has its own limitations. In order to achieve a higher degradation efficacy, integrated processes are being focus in this area. Therefore, the present study is targeted towards the coupling of biodegradation and photocatalytic degradation of p-cresol. The biodegradation of p-cresol was performed via lab isolate Serratia marcescens ABHI001. The obtained results confirmed that ~85% degradation of p-cresol was accomplished using Serratia marcescens ABHI001 strain in 18 h. Consequently, degradation of remaining residue (remaining p-cresol concentration initially used) was also examined in a batch reactor using activated carbon−TiO2 nanocomposite (AC/TiO2-NC) as a catalyst under the exposure of UV radiation. The AC/TiO2-NC was processed via sol-gel technique and characterized by various techniques, namely Brunauer-Emmett-Teller (BET), scanning electron microscope (SEM), X-ray diffraction (XRD), and Fourier transformed infrared spectroscopy (FT-IR). The investigation allowed p-cresol degradation further augment up to ~96% with the help of spectrophotometer trailed by high performance liquid chromatography (HPLC). This study demonstrates that integrated process (biodegradation-photodegradation) is the cost-effective bioremediation process to overcome such kinds of pollutant issues. © 2021, Crown.